Unleashing the Power of Palladium Catalyst: Unveiling the Role in Dew Formation and Anaerobiosis within Anaerobic Jars - Akhmad Sudibya; Indah Widyaningsih (ANATOMICA MEDICAL JOURNAL | AMJ, 2023)
Anaerobiosis is essential for studying and cultivating specific microorganisms, and anaerobic jars are commonly used to create anaerobic conditions. Purpose: To determine the essentiality of a palladium catalyst in creating anaerobiosis. The growth of specific microorganisms and the appearance of water condensate in anaerobic jars with and without the catalyst are observed. Methods: A non-randomized control group design is employed with 10 replications. Ten experiments use a palladium catalyst, while another 10 do not. After a 48-hour incubation, the growth of Pseudomonas aeruginosa, Clostridium tetani, and Bacteroides fragilis is observed. The appearance of water condensate is monitored within a 24-hour incubation period. Results: Water condensate appears within 1.37 to 3.33 minutes in the palladium-contained anaerobic jar, whereas it does not appear without the catalyst. No growth of Pseudomonas aeruginosa is observed with the palladium catalyst, but ten growths occur without it. Eight growths of Clostridium tetani are observed with the catalyst, whereas none occur without it. Bacteroides fragilis does not grow without palladium, but seven growths are observed with the catalyst. Significant differences (p 0.01) in anaerobiosis creation are observed between the two types of anaerobic jars. Conclusion: The presence of a palladium catalyst is crucial for creating anaerobic conditions in anaerobic jars. Without the catalyst, specific microorganisms fail to grow, and water condensate does not appear, indicating ineffective anaerobiosis. These findings stress the necessity of the palladium catalyst for successful anaerobic experiments, highlighting its significance in promoting reliable microbial growth under anaerobic conditions.Keywords: anaerobic, clostridium tetani, palladium, pseudomonas aeruginosa, water condensate.